Mengasah Dampak Penggiring (Nurturant Effect) Nilai Karakter Tanggung Jawab Melalui Integrasi Nilai-Nilai Keislaman dalam Pembelajaran Matematika - Nazliati, Nazliati; Reza, Muhammad (ARITHMETIC: Academic Journal of Math, 2021)
The purpose of this study was to hone the nurturant effect of the value of the character of responsibility on students by integrating Islamic values in mathematics learning. This research is an experimental study using observations and interviews with 5 students of class VIII2 and teachers of SMPN 5 Langsa. Based on the results of the study, it was found that there was a development of the value of the character of responsibility which included a sense of responsibility in completing the tasks that had been given, awareness in helping to solve problems in the group, discipline, and awareness of serving punishment if violating the rules.